Navigating Sudan's conflict: Research insights and policy implications: Proceedings of a conference - Ahmed, Mosab O. M.; Abushama, Hala; Siddig, Khalid; Kirui, Oliver K.; Dorosh, Paul A.; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2024)
This report synthesizes the key discussions and outcomes of the “Navigating Sudan’s Conflict: Research Insights and Policy Implications” conference, held on March 5, 2024, in Nairobi, Kenya. Convening a diverse group of experts in research, development, and humanitarian efforts, the conference aimed to explore actionable solutions for the socioeconomic challenges triggered by Sudan’s ongoing conflict. Participants at the conference delved into the conflict’s adverse impacts on agriculture, markets, employment, and food security, as well as its wider regional impacts. Notably, the conference findings underscore the urgent need for supporting smallholder farmers, stabilizing markets, generating employment opportunities, and enhancing agricultural productivity within a comprehensive recovery strategy. Furthermore, conference participants stressed the importance of innovative data gathering, collaborative policy formulation, international support, and coordination to ensure effective interventions. This report succinctly presents the interventions discussed in the conference’s research and panel discussion sessions, particularly the pivotal insights offered in each to guide policy that will build peace, strengthen resilience, and relaunch and accelerate human and economic development efforts in Sudan.